2016
DOI: 10.1021/acsami.6b10132
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Radiosensitization of Gold Nanospikes via Hyperthermia in Combined Cancer Radiation and Photothermal Therapy

Abstract: Metallic nanostructures as excellent candidates for nanosensitizers have shown enormous potentials in cancer radiotherapy and photothermal therapy. Clinically, a relatively low and safe radiation dose is highly desired to avoid damage to normal tissues. Therefore, the synergistic effect of the low-dosed X-ray radiation and other therapeutic approaches (or so-called "combined therapeutic strategy") is needed. Herein, we have synthesized hollow and spike-like gold nanostructures by a facile galvanic replacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(82 citation statements)
references
References 71 publications
3
77
0
Order By: Relevance
“…Therefore, when combing PTT with RT, the heat generated from PTT can elevate the oxygen level in cancer cells to make the cells more sensitive to radiation, and thus the RT therapeutic effect is availably strengthened. Up to date, a large number of literatures about PTT and RT synergetic therapy can be searched . And we roughly summarized the evolution trends of this synergetic strategy as follows.…”
Section: General Strategies Of Nanomaterial‐mediated Tumor Radiosensimentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when combing PTT with RT, the heat generated from PTT can elevate the oxygen level in cancer cells to make the cells more sensitive to radiation, and thus the RT therapeutic effect is availably strengthened. Up to date, a large number of literatures about PTT and RT synergetic therapy can be searched . And we roughly summarized the evolution trends of this synergetic strategy as follows.…”
Section: General Strategies Of Nanomaterial‐mediated Tumor Radiosensimentioning
confidence: 99%
“…Recently, the nanomaterials that play both roles of photothermal agents and radiosensitizers are widely researched due to their multifunctional properties and simply synthetic methods, such as Au, WS 2 Bi 2 S 3 , Bi 2 Se 3 , ReS 2 , Cu 3 BiS 3 , and WO 3− x nanoparticles. The NIR absorption ability of these nanoparticles allows them to act as photothermal agents for producing significant heat to eliminate tumor, and the high Z atom endows these nanoparticles with the ability to serve as radiosensitizers for accumulating more X‐ray energy in cells.…”
Section: General Strategies Of Nanomaterial‐mediated Tumor Radiosensimentioning
confidence: 99%
“…Nanomaterials used for this combination present high NIR absorbance and can produce a very localized increase in temperature while having a radiosensitizing effect. They are composed of inorganic materials commonly based on copper sulfides, quantum dots, or gold or bismuth containing compounds. In the following section, the application of these materials has been divided into PTT combined with either external radiotherapy or (internal) radionuclide therapy.…”
Section: Photothermal Therapy and Radiotherapymentioning
confidence: 99%
“…NIR irradiation has been combined with X‐ray therapy using a 125 kV X‐ray given in a single 10 Gy dose, resulting in a more than twofold increase of the tumor doubling time when compared with the single therapies. Gold nanospikes have been developed by Ma et al having a 50 nm diameter and excellent stability in PBS (phosphate buffered saline) . In vitro tests have revealed that cell survival is greatly reduced when phototherapy is combined with 6 MV X‐rays, and have led to in vivo studies in which the benefit of the combinational treatment has been evident resulting in pronounced tumor reduction in comparison to the individual treatments.…”
Section: Photothermal Therapy and Radiotherapymentioning
confidence: 99%
“…To overcome these drawbacks, a series of radio-sensitizers such as the two-dimensional (2D) layered transition metal dichalcogenides (TMDs) (MoS 2 , WS 2 , MoSe 2 , and ReS 2 ) and other inorganic materials have been prepared. [8][9][10][11][12][13] Most TMDs were reported to contain high-Z elements that can act as radio-sensitizers to promote the cancer RT effect by absorbing X-rays and concentrating the radiation dose within tumors. [14][15][16] For example, Shen and co-authors have prepared uniform ultrathin rhenium disulfide nanosheets for photothermal RT.…”
Section: Introductionmentioning
confidence: 99%